Before 6 years the father was 3 times older than his son,after 6 years he will be 2 times older.How many years old are the father and the son?
kvnmurty:
the statements should be that: Father was 3 times as old as the Son.... and he will be 2 times as old as his son.. We should not use " older than".
Answers
Answered by
6
Let
= father's age
Let
= son's age
Before
years :
![f-6 = 3(s-6)\implies f=3s-12 f-6 = 3(s-6)\implies f=3s-12](https://tex.z-dn.net/?f=f-6+%3D+3%28s-6%29%5Cimplies+f%3D3s-12)
After
years :
![f+6 = 2(s+6)\implies f=2s+6 f+6 = 2(s+6)\implies f=2s+6](https://tex.z-dn.net/?f=f%2B6+%3D+2%28s%2B6%29%5Cimplies+f%3D2s%2B6)
Subtract second equation from first:
![0=s-18\\s=18 0=s-18\\s=18](https://tex.z-dn.net/?f=0%3Ds-18%5C%5Cs%3D18)
Plug this in second equation and get:
![f=2(18)+6\\f=42 f=2(18)+6\\f=42](https://tex.z-dn.net/?f=f%3D2%2818%29%2B6%5C%5Cf%3D42)
Therefore the father is
years old and the son is
years old
Let
Before
After
Subtract second equation from first:
Plug this in second equation and get:
Therefore the father is
Answered by
6
Let the present (current) ages of father and son be F and S years. We need to form two equations in F and S and then solve them.
Father was 3 times older than his son, 6 years earlier. Actually this statement should be that Father was 3 times as old as the son. 6 years ago, their ages were F-6 years and S-6 years respectively.
=> F - 6 = 3 * (S - 6) --- (1)
After 6 years from now, father will be 2 times as old as his Son. After 6 years their ages are F+6 years and S+6 years respectively.
=> F + 6 = 2 * (S + 6) --- (2)
subtract (2) from (1), we get
- 12 = S - 30 => S = 18 years
Using equation (1) , we get, F - 6 = 3 * (18-6) = 36
Hence, F = father's age = 42 years.
and son's age = 18 years.
Father was 3 times older than his son, 6 years earlier. Actually this statement should be that Father was 3 times as old as the son. 6 years ago, their ages were F-6 years and S-6 years respectively.
=> F - 6 = 3 * (S - 6) --- (1)
After 6 years from now, father will be 2 times as old as his Son. After 6 years their ages are F+6 years and S+6 years respectively.
=> F + 6 = 2 * (S + 6) --- (2)
subtract (2) from (1), we get
- 12 = S - 30 => S = 18 years
Using equation (1) , we get, F - 6 = 3 * (18-6) = 36
Hence, F = father's age = 42 years.
and son's age = 18 years.
Similar questions